mauriciodiazxcv
mauriciodiazxcv
04-05-2018
Mathematics
contestada
6q + q − 3q − 1 = 11 q =
Respuesta :
MiNk2019314
MiNk2019314
04-05-2018
Use algebra to solve for q:
6q+q-3q-1=11q
4q-1=11q
-1=7q
q=-1/7
Answer Link
VER TODAS LAS RESPUESTAS ( 41+ )
ACCESS MORE
Otras preguntas
Which of these characters is NOT condemned by the court in the play? options: Giles Corey John Proctor Reverend Hale Rebecca Nurse
When a private party acts carelessly (or even intentionally) and causes an injury to another party, that injured party has a right to hold the party that caused
Struct and Direct Field Indexing Write a function called ConvertToDecadesAndYears to convert totalYears to decades and years. The decades and years should be re
12x²+28x - 5 = (6x - 1)(_). what’s the factored form ? (6x-1)(__)
The third term in a geometric sequence is -81. The common ratio is 1/3 Write a exponential equation for this sequence.
The sanderling is a shorebird that feeds on insects and small crustaceans such as crabs. Sanderlings that are beyond breeding age often stay in the southern fee
what does a contrast monarchy involve
Who was Louis Timothy?
The state's legal interests are represented at the local level by
E > (6x) = x=1 What is the answer